Educação ambiental e as doenças de veiculação hídrica: a relação entre saúde e meio ambiente - AMBROSIO, Halana Tereza Marques de Jesus (2023)
Environmental Education and its principles involve quality of life in all its aspects, directly linked to public health, with a view to transforming the environment occupied by society into a place favorable to a dignified life. The present study aims to raise awareness among high school students in the city of São Luís/MA to act as multipliers of information about waterborne diseases in their homes and surrounding areas. The research was guided by a systematic review linked to environmental education with a focus on waterborne diseases and their intervening variables and a qualitative-based study, participatory research in which secondary and primary data were collected. The systematic review included 52 articles for analysis; following the items recommended by the PRISMA statement (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) and these were classified into two groups of categories. The qualitative investigation took place in three schools, all offering secondary education, with the sample type selected for convenience and the sample universe composed of students and teachers from the three selected schools, 60 teachers and 100 students were included. The data obtained and analyzed were taken from the answers acquired through questionnaires carried out with the school's teachers, and from data sheets taken from Kahoot applied to the students. In relation to the systematic review, the direct relationship between water-borne diseases and the lack of sanitation, precariousness in basic services in health, housing, and social well-being was specifically highlighted. Participatory research contributed to environmental education, in particular, how it can better integrate information about waterborne diseases through the use of Digital Information and Communication Technologies (DIT). The study also aimed to evaluate and generate pedagogical proposals for environmental education in the dissemination of new information and socio environmental perceptions of young people about waterborne diseases.